Improved interfacial charge transfer and visible light activity of reduced graphene oxide-graphitic carbon nitride photocatalysts - Tiong, Peggy (Royal Society of Chemistry, 2015)
Development of efficient visible light-driven photocatalysts is an important approach towards sustainability. Herein, reduced graphene oxide-graphitic carbon nitride (rGO-gCN) photocatalysts were successfully prepared by in situ photocatalytic reduction of graphene oxide (GO) in the presence of gCN as the photocatalyst. The XPS spectra revealed the presence of N-graphene, which confirmed the interaction between the rGO and the gCN. The rGO-gCN with GO loading amount of 0.1 wt% exhibited almost three times higher photocatalytic activity than gCN for degradation of phenol under visible light irradiation. Fluorescence spectroscopy, EIS, and photocurrent response studies indicated that the presence of rGO significantly promoted the electron-hole separation and improved the interfacial charge transfer on the gCN. These factors played a crucial role in enhancing the photocatalytic activity of the gCN under visible light irradiation.